Continuous flow photooxidation of p-substituted phenols using singlet oxygen in supercritical CO2 applied to telescoped syntheses - Abreu, Bruna (2021)
Interest in photochemical processes both in academia and industry is increasing, but uptake is still limited due to low efficiency and/or scalability of current processes. Photochemical synthesis of highly reactive hydroperoxides so-called ‘p-peroxyquinols’ is of particular interest for synthetic organic chemistry and pharmaceutical manufacturing, given their involvement in the synthesis of antimalarial drugs and complex natural products. Batch synthesis of p-peroxyquinols in large scale can be challenging, given its instability in flammable solvents and long reaction times of up to 48 h. Continuous flow photooxidation of p-substituted phenols using singlet oxygen and supercritical CO2 could be a suitable alternative. In this Thesis, this methodology is explored in telescoped syntheses of compounds with potential pharmaceutical interest.